2018
DOI: 10.12944/cwe.13.3.09
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Heavy Metal Pollution in Soils from Farms in the Vicinity of Durumi Quarry Site in Mpape, Abuja Nigeria

Abstract: Seasonal concentrations of eight total and bioavailable heavy metals (Cr, Cu, Cd, Zn, Mn, Ni, Pb an Fe), along with some physico chemical properties of soil in vegetable farms around the rock quarry in Durumi, Abuja was assessed to know the level of heavy metal pollution of the soil. Control and actual soil samples were collected from depths of 0.0 -5.0cm and 5.0 - 10.0cm during dry and rainy seasons. Heavy metal concentrations varied inconsistently in samples and control. Dry season levels of Zn(5.20mg/kg), M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
1
Order By: Relevance
“…However, at sampling points 100 m and 200 m, the organic matter content was generally lower than that reported by E ong and Gilbert (2012) in a similar study. The percentage of sand, silt, and clay obtained was similar to those obtained by Ojo et al (2018) and Moses & Edet (2013). Results obtained revealed a decline in soil quality near the quarry, similar to the reports of Igwenagu-Ifeanyi et al (2021).…”
Section: Physiochemical Analysis Of Soil and Water Samplessupporting
confidence: 89%
“…However, at sampling points 100 m and 200 m, the organic matter content was generally lower than that reported by E ong and Gilbert (2012) in a similar study. The percentage of sand, silt, and clay obtained was similar to those obtained by Ojo et al (2018) and Moses & Edet (2013). Results obtained revealed a decline in soil quality near the quarry, similar to the reports of Igwenagu-Ifeanyi et al (2021).…”
Section: Physiochemical Analysis Of Soil and Water Samplessupporting
confidence: 89%
“…Emori et al (2015) reported higher concentration of Cadmium in dumpsites in Calabar metropolis when compared to mechanic workshops. Cadmium levels observed were higher than the observations of Ayodele et al (2014) who reported cadmium levels below detectable limits for soils around granite quarries at Ikole-Ekiti, Nigeria, and a lower range of 0.06-0.07 was also observed for Durumi quarry site Mpape Abuja, Nigeria by Ojo et al (2018).…”
Section: Results and Discussion Heavy Metals Concentration In Dumpsit...contrasting
confidence: 71%
“…The study also assessed the ecological risk of heavy metals in the soil, concluding that the contamination poses a significant risk to the environment and human health. Ojo et al (2018) contributed to the understanding of heavy metal pollution by assessing soils from farms in the vicinity of the Durumi Quarry Site in Mpape, Abuja, Nigeria. The study focused on the seasonal concentrations of total and bioavailable heavy metals, along with the physicochemical properties of the soil in vegetable farms around the rock quarry.…”
Section: Heavy Metals In Watermentioning
confidence: 99%